COMPARISON OF TRAINING PURSED LIP BREATHING AND BALLOON BLOWING ON THE INCREASING OF RESPIRATORY MUSCLE STRENGTH, RESPIRATORY RATE AND THE INCREASING OF OXYGEN SATURATION IN COPD AT THE MAKASSAR COMMUNITY LUNG HEALTH CENTER - Junaidin Junaidin (Stikes Graha Edukasi Makassar, 2019)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is one of lung disorders that affect air movement from and out of the lung, this can lead to hypoxemia and hypercapnia due to the occurrence of respiratory muscle weakness and obstruction. As the result, it will increase airflow resistance, pulmonary hyperinflation also ventilation and perfusion imbalances . One of the pulmonary non-pharmacological treatments that can be given to COPD patients includes the pursed lip breathing exercise (PLB) technique and blowing balloons. This rehabilitation exercise aims to improve lung function, prevent damage, and improve quality of life. Method: This study was a Quasi-Experimental study, with pre-posttest design in two different comparison groups. Results: Increased breath muscle strength and significance difference on the third day after the intervention of balloon blowing (median = 5870) and PLB (median = 5830) obtained p value <0.001, while the seventh day after the balloon blew intervention (median = 5980) and PLB ( median = 5880) Significant differences were obtained with a value of p <0.001. Conclusion: Blowing balloons is very significant in increasing breath muscle strength in comparison to PLB in COPD patients,.